Frontalis sling surgery - pediatric versus adult population: characteristics and outcomes - Arnon, Roee; Rosner, Mordechai; Priel, Ayelet; Sagiv, Oded; Landau-Prat, Daphna; Rock, Oded; Armanik, Sharon; Shalamaev, Yonatan; Arazi, Mattan; Zloto, Ofira (BMC ophthalmology, 2024)
Purpose Frontalis sling surgery is a common method for ptosis correction for both pediatric and adult populations. This study aims to compare the characteristics and outcomes of this surgery in these two populations. Methods A retrospective cohort study. Patients who underwent frontalis sling surgery between the years 2009 and 2024, with complete medical chart data, and had at least a one-month follow-up period were included. Age, gender, ptosis type, type of sling, complications, and re-surgery were analyzed. Results A total of 62 patients were included, with 41 patients in the pediatric group and 21 patients in the adult group. The mean age was 4.7 ± 5.0 and 46.04 ± 18.33 years old in the pediatric and adult groups, respectively. The most common etiology of ptosis in the pediatric group was simple congenital (70%), while the most common etiology in the adult group was myogenic ptosis due to a systemic condition (47%) ( p < 0.001). Baseline pre-operative MRD1 (marginal reflex distance 1) was lower in the adult group compared to the pediatric ( -0.37 ± 1.21 mm vs. 0.36 ± 0.65 mm respectively (t-test, p = 0.04)). However, the mean change in MRD1 (pre-operative to postoperative) was not significantly different for both groups (t-test, p = 0.5). A higher rate of sling extrusion was observed among the adult group (0% of pediatrics vs. 14% of adults, chi-square, p = 0.013). A higher number of previous sling surgeries were found to be positively correlated ( r = 0.672) with overall postoperative complications (Pearson correlation. p = 0.006). Conclusion Frontalis sling surgery varies between adult and pediatric patients regarding etiology, preoperative findings, surgical approach, and complications. Adults experienced higher rates of complications such as sling extrusion and dry eye. Moreover, an increased number of previous sling surgeries was associated with a rise in postoperative complications such as suture dehiscence, extrusion, and granuloma formation. Consequently, frontalis sling procedures should be regarded as a last resort for ptosis correction in adults due to the elevated risk of complications.